fs LA-ICP-MS를 이용한 메주의 유해중금속(Cd, Pb) 신속 분석법 개발 - 신희창; 최지혜; 김용경; 김대중; 안재민; 김성연; Shin, Hee-Chang; Choi, Ji-Hye; Kim, Yong-Kyoung; Kim, Dae-Jung; An, Jae-Min; Kim, Sung-Youn (Han'gug sigpum wi'saeng anjeonseong haghoeji, 2022)
The official analytical method for the analysis of harmful heavy metals in Meju, distributed in Korea, employs a strong acid to decompose the organic components. This analysis is time consuming and harmful to the users and/or the environment. This study aimed to develop a new pre-treatment technology using laser ablation, to rapidly analyze harmful heavy metals without using strong acids. The results obtained from this method were validated by the National Institute of Food and Drug Safety Evaluation guideline (NIFDS, 2016). Moreover, a comparison of the two methods showed that the analytical time for 55 Meju samples was shortened by 96% or more in the new method. The results showed no significant difference in the recovery ranging from 90-120%. The proposed method proved suitable for detecting harmful heavy metals in Meju. 국내 유통되는 메주의 유해중금속 분석을 위한 기존의 분석법은 강산을 사용하여 유기물을 분해하기 때문에 분석시간이 장시간 소요되며, 사용자 또는 환경에 유해한 영향을 끼친다. 이러한 단점을 개선하기 위해서 강산을 사용하지 않고 신속하게 분석할 수 있는 laser ablation 전처리 기술을 활용하여 신속 분석법을 개발하였다. 개발된 분석법의 유효성 검증을 실시한 결과, 식품의약품안전평가원 가이드라인의 화학적 검증 요소들을 모두 만족하였다. 또한 기존 분석법과 개발된 신속 분석법을 비교 평가하였다. 메주 시료 55점에 대한 분석 시간은 기존 분석법 대비 96% 이상 단축시킬 수 있었고, 분석 결과는 90-120% 범위의 회수율로 유의적 차이가 없었다. 개발된 신속 분석법은 메주 중 유해중금속 관리에 적합할 것으로 판단된다.